THE INFLUENCE OF NIGHT WORK, DIET, ALCOHOL CONSUMPTION, AND CIGARETTE SMOKING ON THE STRESS LEVEL OF SECURITY WORKERS: Uticaj noćnog rada, ishrane, alkohola i pušenja na nivo stresa kod radnika obezbeđenja - stanković, nada (Acta medicae Medianae, 2026)
Night work, characteristic of occupations such as security guard work, presents unique challenges to workers’ health on biological, psychological, and social levels. Circadian rhythms are disrupted due to night shifts, leading to sleep disorders, increased stress, and metabolic imbalances. This study analyzes how age group, night work, smoking, alcohol consumption, diet, and body mass index (BMI) affect stress levels among security workers. A sample of 154 workers was assessed through surveys and standardized stress measurement tools. Key findings indicate significant effects of night work, age, smoking, alcohol consumption, and BMI on stress levels, with a balanced diet being associated with reduced stress. Practical suggestions include promoting healthy habits to reduce stress and improve workers’ overall health. Night work, typical jobs such as security guard work, poses distinct challenges to worker health on biological, psychological, and social levels. Circadian rhythms, which regulate biological processes in the body, are disrupted due to shift work, especially night shifts, potentially leading to sleep disorders, increased stress, metabolic disturbances, and poor eating habits. Lack of sleep and improper diet contribute to reduced work performance and increase the risk of chronic illnesses such as diabetes and cardiovascular diseases. Additionally, alcohol and cigarette use are often coping mechanisms for stress and insomnia, further exacerbating health issues. The research aimed to analyze how different age groups, night work, smoking, alcohol consumption, diet, and BMI influence stress levels in security workers, with a special focus on how night shifts shape health habits and overall well-being. The study was conducted on a sample of 154 workers from various age groups and work environments, using a survey to assess work-related habits, health, diet, smoking, alcohol use, and BMI measurement. The results show that age group and night work significantly affect stress levels; older workers and those on night shifts report higher levels of stress. Smoking and alcohol use further increase stress, while BMI shows a significant impact on stress, particularly during night shifts. A balanced diet is associated with reduced stress. The conclusion is that night work, age, smoking, alcohol consumption, BMI, and diet significantly influence stress levels among security workers, and changes in unhealthy habits can help reduce stress.